Perceived Effectiveness of Strategies Used by Teachers to Foster Social Skills among Students with Intellectual Disability - Muhammad Usman Zia; Rukhsana Bashir; Fatima Munir (Review Journal of Social Psychology & Social Works, 2024)
This study explores teachers’ perceptions of the strategies used to develop social skills among students with intellectual disabilities. Using a survey design, data were collected from 54 special education teachers in Punjab, Pakistan. The findings reveal that Cooperative Learning and Collaboration with Parents are the most frequently used strategies, while Reinforcement and Positive Feedback is perceived as the most effective. Significant differences were observed between government and private sector teachers, with government teachers rating both the use and effectiveness of strategies more positively. The results emphasize the importance of personalized, interactive strategies and the potential for increased integration of technology-based interventions.